THE EFFECT OF INFLATION AND UNEMPLOYMENT ON THE ECONOMIC GROWTH OF TUAL CITY - Djodding, Ikram Mubarak (Journal of Management Small and Medium Enterprises (SMEs), 2024)
Inflation turns out to have quite a big impact on the economic growth of Tual City. High inflation rates can hinder economic development in the area. In addition, unemployment greatly hinders economic growth. Low economic growth can be caused by high levels of unemployment because it reduces investment and consumer confidence. These results have major implications for the city government and related stakeholders in Tual City in their efforts to develop sound economic policies. Sustainable economic growth requires measures to control inflation and reduce unemployment rates. Good monetary policy as well as training and job search programs can help solve this problem. This research has several problems, including the small sample size and the potential impact of uncontrolled variables on economic growth. Research on the influence of inflation and unemployment on economic growth in Tual City can be expanded by considering additional relevant variables. Keywords: Inflation; Unemployment; Economic growth; Tual City; Multiple Linear Regression